Rat IgG mediated circulatory cell depletion in mice requires mononuclear phagocyte system and is facilitated by complement. Issue 3 (22nd January 2020) - Sun, Donglei; Sun, Peng; He, Shenghu; Shi, Meiqing
Abstract: Application of exogenous Abs targeting cell surface Ags has been widely used as an experimental approach to induce cell depletion or to inhibit receptor functionality. Moreover, Ab therapy is emerging as one of the mainstream strategies for cancer treatment. Previous studies on the mechanisms of Ab-mediated cell depletion mainly employed Abs from the same species as the research subject. However, there has been a recent trend toward using xenogeneic (cross-species) Abs to achieve cell depletion or block receptor-ligand interactions; with rat Abs used in mice being the most common approach. Considering the molecular differences in Abs from different species, the mechanism(s) of xenogeneic Ab-mediated cell depletion is likely to be different than species-matched Ab supplementation. The current work describes our efforts to identify the mechanism of rat anti-mouse Ly6G (clone: 1A8) mAb mediated depletion of mouse neutrophils. The results showed that neutrophils circulating in the blood but not those in the bone marrow are depleted, and depletion depends on mononuclear phagocyte system, especially liver Kupffer cells that efficiently capture and phagocytize targeted cells. Interestingly, whereas species-matched Ab depletion does not require complement functionality, we found that complement activation significantly facilitates cross-species neutrophil depletion. Finally, we found that some rat mAbs (anti-C5aR, anti-CD11a, anti-CD11b, and anti-VLA4) used to block cell surface receptors also induce cell depletion. Thus, our work strongly recommends controlling for cell depletion effect when using these Abs for receptor blockade purposes.